(untitled) (The Pakistan Development Review, 2010)
This paper tests an idea from relational contracting theory [Macauley (1963); North (1990); Greif (1994); Kranton (1996)] that informal relationships can substitute for formal contract enforcement through the judicial system, from the analysis of a new survey of the surgical instrument cluster in Sialkot, Pakistan. Inter-firm trust is thought to lead to reduced transaction costs (a passive benefit of a cluster). Considered here are exchanges of goods between clustered suppliers and their customers, who are either members of the cluster or firms that interact frequently with it. Inter-firm trust is measured as the amount of trade credit offered to customers. The results show that suppliers are more likely to offer trade credit when they believe in the effectiveness of formal contract enforcement and when they participate in business networks (proxied by inter-firm communication). There is also some evidence that customer lock-in helps to develop inter-firm trust since firms give more credit when relationships are of longer duration, and as locked-in customers are less able to find alternate suppliers.